HLA-A allele frequency and haplotype distribution in the Dravidian tribal communities of South India - R. Thomas, M. Banerjee (Indian Journal of Human Genetics September-December 2005 Volume 11 Issue 3, 2005)
The tribal communities of South India are considered to be the original inhabitants of the Indian subcontinent, belonging to the most primitive Dravidian speaking communities. These Dravidian speaking forest dwelling tribal populations have remained isolated from any intermingling with other non-tribal communities. AIMS AND OBJECTIVES: We propose to understand the evolutionary processes mediated by molecular, functional and immunological information based on human leukocyteantigen (HLA) genetic system. MATERIAL AND METHODS: The HLA-A diversity wasanalyzed in seven Dravidian tribal populations namely Malapandaram, Paniya, Kurichiya, Kanikkar, Adiya, Kattunaikka and Kuruma of Kerala, South India using the PCR-SSP method. The tribal communities were compared with a group comprising of random non-tribal Dravidian samples of southern India.